2014
DOI: 10.1016/j.jpainsymman.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prophylactic Subcutaneous Fentanyl on Exercise-Induced Breakthrough Dyspnea in Cancer Patients: A Preliminary Double-Blind, Randomized, Controlled Trial

Abstract: Context Dyspnea is one of the most distressing symptoms in cancer patients, and often worsens with breakthrough episodes on exertion. We hypothesized that fentanyl given prophylactically may alleviate breakthrough dyspnea. Objectives To determine the feasibility of conducting a randomized trial of subcutaneous fentanyl in cancer patients, and examine the effects of fentanyl on dyspnea, walk distance, vital signs and adverse events. Methods In this double-blind, randomized, controlled trial, we asked ambula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 18 publications
2
76
2
1
Order By: Relevance
“…(13, 16) In a double-blind, randomized controlled trial, we found that prophylactic subcutaneous fentanyl given at proportional dose of 15-25% of MEDD was safe and significantly improved dyspnea at rest, dyspnea at the end of 6MWT, walk distance, fatigue and respiratory rate in intra-individual comparison. (13) In another double-blind randomized controlled trial, FPNS at proportional dose of 15-25% of MEDD was also found to significantly improve dyspnea at rest, dyspnea at the end of 6MWT, and walk distance. (16) Interestingly, the walk distance and the dyspnea at rest did not improve significantly in the current study, which may be related to the differences of medication, timing of administration and variability among patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…(13, 16) In a double-blind, randomized controlled trial, we found that prophylactic subcutaneous fentanyl given at proportional dose of 15-25% of MEDD was safe and significantly improved dyspnea at rest, dyspnea at the end of 6MWT, walk distance, fatigue and respiratory rate in intra-individual comparison. (13) In another double-blind randomized controlled trial, FPNS at proportional dose of 15-25% of MEDD was also found to significantly improve dyspnea at rest, dyspnea at the end of 6MWT, and walk distance. (16) Interestingly, the walk distance and the dyspnea at rest did not improve significantly in the current study, which may be related to the differences of medication, timing of administration and variability among patients.…”
Section: Discussionmentioning
confidence: 97%
“…6MWT were carried out following guidelines from the American Thoracic Society and have been described in detail. (13, 28) We also assessed both dyspnea and fatigue using the 0-10 modified Borg scale before and after each 6MWT, and measured the distance walked every minute. (28) The minimal clinically significant difference was 1 point for both the NRS and modified Borg scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another trial, doses of parenteral fentanyl given prophylactically, proportional to opioids given chronically (15e25%), were safe and effective. 20 This study suggests that fentanyl products could be given before an expected trigger, as it is for preventing predictable breakthrough pain, for example, before starting an activity.…”
Section: Treatment Of Breathlessness and Episodic Breathlessnessmentioning
confidence: 92%
“…Interestingly, exercise has been used as a model for inducing episodic breathlessness. 20 It could be surprising that episodic breathlessness is more likely in patients with higher Karnofsky Performance Status scores. Paradoxically, patients with a higher Karnofsky score are more physically active and, therefore, more likely to experience episodes of breathlessness on exertion.…”
Section: Factors Inducing Episodic Breathlessnessmentioning
confidence: 99%